Leachability Of Arsenic From Wastes Of Arsenic Removal Units Using Modified Toxicity Characteristic Leaching Procedure - Islam, Md Shafiqul; Al Mamun, Md Abdullah; Islam, Md Nazmul (Journal of Life and Earth Science, 2012)
The present study evaluated the leaching of arsenic from sludge/waste of seven SONO filters that were operated in Rajarampur of Chapai Nawabganj district. For this, Toxicity Characteristic Leaching Procedure (TCLP) test was performed. To understand actual leaching of arsenic, a Simulated Natural Column (SNC) that is comparable to natural mature landfill was devised. Total arsenic concentration (AsT) was measured by HG-AAS. The studied arsenic waste/sludge, having 7.0-9.2% solid content, were alkaline in nature (pH values of 7.9-8.7) and had arsenic and iron concentrations of 4.54-5.50 and 480-1039 mg kg-1 respectively. The TCLP test reveals that 6.4-19.4% (average 14%) of arsenic was leached from the waste (average leachate AsT before and after TCLP were 5.04 and 0.71 mg kg-1 respectively). After 102 days of continuous operation in SNC, AsT in the leachate was found to be 0.223 mg L-1, although initial AsT was 0.350 mg L-1. It was observed that AsT in SNC leachate increased up to 54 days (corresponding to 1.741 mg L-1) and then decreased in reciprocal quadratic pattern. Comparison shows that TCLP underpredicts 14.2% of arsenic leaching than that of SNC. Since leachate AsT in both methods did not exceed the USEPA regulated level of 5 mg L-1, the studied waste/sludge was not hazardous. DOI: http://dx.doi.org/10.3329/jles.v6i0.9716 JLES 2011 6: 19-26